Motivasi Kerja Aparatur Bidang Ketentraman Dan Ketertiban Umum Di Dinas Satuan Polisi Pamong Praja Kabupaten Pasangkayu - Anwir, Anwir; Tinggogoy, Filo Leonardo; Rapi, Muh (PARADIGMA : Jurnal Administrasi Publik, 2023)
The purpose of this research is to determine the work motivation of officers in the field of peace and public order in the civil service police unit in Pasangkayu Regency. The informants in this research were officials from the Civil Service Police Unit Office. Apart from that, to determine work motivation, this research data consists of primary data and secondary data obtained directly through field research (interviews). The data was analyzed using the results of interviews with the Civil Service Police Unit Service. Head of Service, Service Secretary, General and Civil Service Sub-Division, Peace and Public Order Section and Staff. The results of the research show that to determine the work motivation of officers in the field of peace and public order in the civil service police unit in Pasangkayu Regency. The author chose a theory that is considered more suitable to be applied to government organizations, in this case the Pasangkayu Regency Civil Service Police Service, if implemented simultaneously, good service quality will be realized, is David McClelland's theory in Mangkunegara (2001: 97 - 98), namely: The need for Achievement, Need for Power, and Need for Affiliation. What was highlighted by the informants from the results of interviews with the apparatus itself was that work motivation which was considered not yet optimal in its implementation was the need for achievement and the need for will power while the indicators/dimensions of Affiliate Needs whose results are still not being implemented well. The influencing factors are the capability of human resources which is an important aspect of the smooth running of public services in the organization.